2021
DOI: 10.4062/biomolther.2020.054
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leptin in the Association between Obesity and Psoriasis

Abstract: Adipose tissue secretes many adipokines which contribute to various metabolic processes, such as blood pressure, glucose homeostasis, inflammation and angiogenesis. The biology of adipose tissue in an obese individual is abnormally altered in a manner that increases the body’s vulnerability to immune diseases, such as psoriasis. Psoriasis is considered a chronic inflammatory skin disease which is closely associated with being overweight and obese. Additionally, secretion of leptin, a type of adipokine, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 119 publications
0
33
0
2
Order By: Relevance
“…In addition, we found that M5 and T3 could prevent HFD-induced weight gain and effectively protect against hepatocellular injury. Leptin is a type of adipokine, that can protect T lymphocytes from apoptosis and regulate T cell proliferation, increase the proliferation of naive T cells, and reduce the proliferation of memory T cells (Hwang et al, 2020). The function of the leptin pathway is to ensure a balance between body weight and energy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that M5 and T3 could prevent HFD-induced weight gain and effectively protect against hepatocellular injury. Leptin is a type of adipokine, that can protect T lymphocytes from apoptosis and regulate T cell proliferation, increase the proliferation of naive T cells, and reduce the proliferation of memory T cells (Hwang et al, 2020). The function of the leptin pathway is to ensure a balance between body weight and energy.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, numerous findings confirm a significantly higher concentration of leptin among psoriasis patients, especially in its moderate and acute form [ 24 , 25 ], in which treatment with anti-cytokine agents is recommended [ 18 ]. Secondly, a positive correlation was noted between the concentration of leptin in the serum and BMI [ 26 , 27 ], while the influence of leptin on receiving the response to the applied treatment and maintaining the period of disease remission, was also determined [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such pathways include the Janus kinase 2/signal transducer, the activator of transcription factor 3 (JAK2/STAT3) signaling [ 31 , 32 ], and the mitogen-activated protein kinase (MAPK) family (p38 MAPK), as well as the stress activated c-Jun N-terminal kinase (JNK) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathways [ 31 , 33 ], which together explain the multiplex inflammatory responses and the wide repertoire of the responding cells in the skin that are not only immune cells but also keratinocytes, fibroblasts, and sebocytes [ 34 ]. Importantly, besides murine studies describing an increased inflammation in the imiquimod-induced psoriasis-like skin in leptin deficient (ob/ob) mice [ 35 , 36 ], LEPR together with leptin was found to have significantly higher expression levels in the skin of severe psoriatic patients, even with normal BMI, compared to patients with mild–moderate psoriasis and controls in histological studies [ 28 ]. Moreover, leptin mRNA expression in the subcutaneous adipose tissue also positively correlated with the severity of psoriasis and the BMI in obese psoriatic patients [ 37 ] suggesting that leptin-induced signaling mediates both local as well as systemic changes.…”
Section: Discussionmentioning
confidence: 99%